برصغیر میں مسلم فکری انحرافات کے مذہبی اسباب ومحرکات: Religious Causes of the Muslims Deviant Thoughts in the Subcontinent (Al-Qamar, 2023)
After a very sorrowful martyrdom of Ḥadrat Uthman, the entire Ummah was enmeshed in the net of deviation of religious thoughts. During the reign of Ḥadrat Ali, the political disruption was in full swing the deviant thoughts got time to be nurtured and flourished and the unity of Umma was damaged very badly. No doubt many religious factors were there, but the Ummah stuck to the teachings of the holy Quran and Sunnah and were proud of being the followers of the companions. But, in the later years, people devised a lot of new beliefs that were quite apart from that main system of beliefs of the Muslims and they were commonly known as Khawārij and they were named as they extended themselves from the mainstream of the Muslims. With the advent of Islam by the Muslim commanders like Muhammad bin Qasim, the Muslim deviant thoughts came simultaneously and developed there in the sub-continent. With the development of these thoughts, people even averred to be a Mahdi and a prophet (false) as well; this article is to present an analytical study of the Muslims deviant thoughts in the sub-continent.
Keywords: Ḥadrat Uthman; Ḥadrat A’lī; Muslim Thoughts; Deviation; Religious; elements; sub-continent